MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM INTEGRATIF - Ida Farida Isnaeni (IAIN Padangsidimpuan, 2016)
National education aims at realizing the Indonesian people who is faithful and devoted. Achievement of these objectives need to be supported by the pattern of implementation of learning in integrative educational institutions. The integrated learning model is the model of lerning to combine several sub-subjects with another sub-subjects in a subject; or even between subjects. Expansion of the responsibility of coaching faith and taqwa who had been on religious teachers, and now should be for all teachers and other school components. This responsibility does not mean that the non-religion teachers teach faith and taqwa in the subject of their teaching, but they should support their learning to the value of that values, next to the substance of their subjects. This step is based on the principle that every subject must contain three elements integratedly, they are their subject of teaching, scientific and value. So, the teaching must have values that support the learning of characters (character / moral).